PARTISIPASI PEREMPUAN DALAM KONSERVASI LAHAN DI DESA KALISORO KECAMATAN TAWANGMANGU KABUPATEN KARANGANYAR - Retno Setyowati; Raden Kunto Adi (Universitas Sebelas Maret, 2008)
The Basic of this research was women in agriculture and food production used of role on key position. Womens role on almost from all production process from preparation of seed, seedbad, planting, treatment, and harvest, include to participate into marketing of product. But the womens job in agriculture sector maked to not real. The objectives this research was to know of roles, access, controls and benefits for womens in land tenure. The basic method was descriptive. Location and respondent was purposive sampling. The data analysis with percentage analysis. cross tabulation and rates of values. The results of this research were shows that womens participation in decision making at land tenure is real. although mens participation were biggest. Womens participation in land tenure as like planting, cultivate, cutting of grass, drying of land, and els Alocation of time works that used for land tenure was bigger than seven hours of day. Womens also participation in second jobs at family although just small, depend of second jobs at household. Womens access on trainings to growing up of land was not there. Trainings was still just for mens or husbands. Womens participation in credits or capital was still there, that many of credits that advanced. Womens participation in sales productions and pricing of productions of household. The money from yield of harvest gave to all of husbands to their wifes, because husbands to hand over that financial household to their wifes. Control of husband at costs of household was still there. Profit from yield or h;1rvcst was not used by wife to private used of priority, but used for household as like to needs of days of household, costs of school for childrens, costs of social community. Womens was puts to benefits of profits from yields of harvest that put to fill of needs of household, although sometimes was not enough, womens that accept with sincere.